Critical Reflections on the Use of Imprecatory Psalms in Nigerian Indigenous Churches: Case Study of Church of the Lord, Aladura - Alagbe, Olusola O. (Theologische Universiteit Kampen, 2024)
Masterthesis Intercultural Reformed Theology
free